Bilateral macular haemorrhages secondary to hepatitis-associated aplastic anaemia, treated with Nd:YAG laser posterior hyaloidotomy. (1st December 2011) - Ranganath, Akshatha; Mariatos, George; Thakur, Shakti
Abstract : Hepatitis-associated aplastic anaemia (HAAA) is an uncommon but distinct variant of aplastic anaemia in which pancytopenia and bone marrow failure appears 2–3 months after an acute attack of hepatitis. Although bilateral vision loss may rarely be the initial presentation of aplastic anaemia, no such report is known in HAAA. Here the authors report such a case presenting with large premacular subhyaloid haemorrhages secondary to severe anaemia and thrombocytopenia. Anaemic hypoxic damage to the vessel wall together with increased cardiac output and low platelet counts are interacting causal factors in the development of bleeding. Though these haemorrhages are benign and usually improve spontaneously, the presence of blood may cause permanent macular changes before it resolves. Posterior hyaloidotomy enabled rapid resolution of premacular subhyaloid haemorrhage thereby restoring vision and preventing need for vitreo-retinal surgery. These patients should be advised to refrain from valsalva manoeuvres, ocular rubbing and vigorous exercise to prevent ocular morbidity.